Experimental Study on the Effect of Brittleness on the Dynamic Mechanical Behaviors of the Coal Measures Sandstone - Junce Xu; Hai Pu; Ziheng Sha (Advances in Civil Engineering)
As one of the most crucial mechanical parameters of the rock materials, the effect of brittleness on the deformation and failure is of great practical significance for geotechnical construction and disaster prevention and mitigation. In this paper, the deformation and failure behaviors of the different brittle samples under dynamic loading were investigated using a split Hopkinson pressure bar (SHPB) experimental system. Besides, scanning electron microscopy (SEM) was also employed to study the relationship between the microscopic failures and rock brittleness and strain rate effects. The results revealed that the brittleness indexes BI3 and BI5 of the samples under uniaxial compression follow a linearly decreasing trend affected by the temperature changes, while the brittleness of the sample shows an increasing trend with the increase of strain rate under the dynamic loading. Also, the decline in the brittleness leads to an increase in the prepeak yield deformation phase of the sample under dynamic loading; after the peak point, the sample failure mode transitions from type I to type II with self-sustaining failure. Moreover, it was found that the dynamic strength increase factor presents a negative correlation with the sample brittleness. Finally, the macroscopic failure mode of the sample changes from split failure with multiple cracks to shear failure with few cracks due to the effect of decreasing brittleness. The failure surface of the sample gradually becomes smooth with the increase of brittleness, which manifests as a decrease in microcracks, and the gradual increase of the strain rate makes the failure surface rough, accompanied by an increase in microcracks.